Fusion Protein Cleavage Site Containing Three Basic Amino Acids Attenuates Newcastle Disease Virus in Chicken Embryos: Use as an in ovo Vaccine - Feng, Helong; Shang, Yu; Li, Li; Sun, Xiuxiu; Fan, Sanling; Ren, Xiangfei; Xu, Yingying; Zeng, Zhe; Hu, Xingxing; Cheng, Guofu; Wen, Guoyuan (Frontiers in Microbiology, 2022)
In ovo vaccination is an attractive immunization strategy for the poultry industry. However, although most live Newcastle disease virus (NDV) vaccine strains, such as LaSota and V4, can be used after hatching, they are pathogenic to chicken embryos when administered in ovo. We have previously reported that NDV strain TS09-C is a safe in ovo vaccine in specific-pathogen-free and commercial chicken embryos because it is attenuated in chicken embryos. However, the molecular basis of its attenuation is poorly understood. In this study, we firstly evaluated the safety of chimeric NDV strains after exchanging genes between strains TS09-C and LaSota as in ovo vaccines, and demonstrated that the attenuation of NDV in chicken embryos was dependent upon the origin of the fusion (F) protein. Next, by comparing the F protein sequences of TS09-C strain with those of LaSota and V4 strain, the R115 in cleavage site and F379 were found to be unique to TS09-C strain. The mutant viruses were generated by substituting one or two amino acids at position 115 and 379 in the F protein, and their safety as in ovo vaccine was evaluated. Mutation in residue 379 did not affect the viral embryonic pathogenicity. While the mutant virus rTS-2B (R115G mutation based on the backbone of TS09-C strain) with two basic amino acids in F cleavage site, was pathogenic to chicken embryos and similar with rLaSota in its tissue tropism, differing markedly from rTS09-C with three basic amino acids in F cleavage site. Together, these findings indicate that the F protein cleavage site containing three basic amino acids is the crucial determinant of the attenuation of TS09-C in chicken embryos. This study extends our understanding of the pathogenicity of NDV in chicken embryos and should expedite the development of in ovo vaccines against NDV.